Lossy Compression of Biometric Images Implemented Using Floating Point DSP Processor - Azuwam, Azuwam Ali Alhadi; Ahmad, Muhammad Imran; Md Isa, Mohd Nazrin; Ilyas, Mohd Zaizu; Raja Ahmad, Raja Abdullah (MATEC web of conferences, 2017)
In this paper, several numbers of biometric images are compressed in order to reduce the number of bits needed in representing an image with conservation of image quality. Biometric images compression is important to solve the problem of efficiently transmitting data and storing large number of biometric images in low capacity of memory device. Biometric images are compressed using two techniques which are DCT and Quantization. The compression algorithm is implemented on general purpose computer and DSP processor in order to compare between both of them in terms processing time and evaluate the performance of this technique by measuring the difference between the original image and reconstructed image using PSNR, SSIM and MSE. Experimental results show DCT algorithm produces a high quality for reconstructed images with acceptable compression rate in terms of quality level is more than 50%. Furthermore, implementing the proposed algorithm using DSP board achieves better performance in terms of processing time compared with PC based.